Analysis of State Court Of Batang Decision Number: 4 / Pid.Sus / 2018 / Pn Btg on Felony Obscenity Crime Based On Islamic Criminal Law - Bagus Langgeng Prasetiyo; Gunarto Gunarto; Munsharif Abdul Chalim (Magister of Law, Faculty of Law, Universitas Islam Sultan Agung, 2019)
In the case of sexual crimes where the child victim, the victim could be the driving factors behind crime. For example, we say today is increasingly widespread promiscuity, children have been left free in terms of promiscuity and lack of supervision of their parents, the They were released along with others, go anywhere. So, with their innocence, they could be trapped in one association and exploited by the parties or adults who are not responsible. In such circumstances, the public, law enforcement officers and even a State shall be estimated on the protection and supervision of children, especially where children as crime victims of sexual crimes indeed very concerned and could undermine future portion of the prospective successor to the nation.Therefore, the authors are interested in writing this thesis titled